Further investigations into the origin of credit score cutoff rules - Ryan Bubb; Alex Kaufman (Federal Reserve Bank of Boston, 2011)
Keys, Mukherjee, and Vig (2010a) argue that the evidence presented in Bubb and Kaufman (2009) is based on an inappropriate pooling of loans sold to private-label securitizers with loans sold to the government sponsored enterprises (GSEs). In this paper we investigate the issues raised by the authors and conclude that they do not change our basic analytical approach or conclusions. We examine samples that do not pool together loans sold to these two types of purchasers - a sample of loans bought by the GSEs, a sample of loans originated in 2008-2009 after the private-label market collapsed, and a sample of jumbo loans - and find discontinuities in the number and default rate of loans at credit score cutoffs in the absence of corresponding discontinuities in the securitization rate. We also examine a key assumption underlying their estimates - that no loans are both at risk of being sold to the GSEs and at risk of being sold to private-label securitizers - and show that the data are inconsistent with that assumption. We find that 18 percent of conforming loans in our sample at some time switched between GSE and private-label ownership, demonstrating that the GSEs and private-label securitizers competed for the same loans. Additionally, we show that lender screening cutoffs grew steadily over the period 1997-2010 during which the private-label market rose and collapsed.
Keywords: D82; G01; G18; G21; G24; G28; 330